2021
DOI: 10.1007/s11845-021-02806-w
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the safety and effectiveness of telephone triage in prioritising patient visits to an ophthalmic emergency department — the impact of COVID-19

Abstract: Background During the COVID-19 crisis, a new nurse and doctor-led telephone triage model of care was evaluated as a method of prioritising essential visits to the ophthalmic accident and emergency department in the Royal Victoria Eye and Ear Hospital. This new method of service is known as “Telehealth” or “E-Health”. Aims To assess the safety and efficacy of a Telehealth model of care ultilised during the COVID-19 pandemic. Methods A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Several studies have reported that telehealth interventions offer continuity-of-care advantages 13,25,38 . Even when social isolation was mandated, nurses could navigate patients' symptoms, thereby reducing the absence of continuous care and making it possible to both increase patients' quality of healthcare and significantly reduce their emergency department visits 26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that telehealth interventions offer continuity-of-care advantages 13,25,38 . Even when social isolation was mandated, nurses could navigate patients' symptoms, thereby reducing the absence of continuous care and making it possible to both increase patients' quality of healthcare and significantly reduce their emergency department visits 26 …”
Section: Resultsmentioning
confidence: 99%
“…Of these, seven additional studies were excluded because they did not meet inclusion criteria; for example, interventions were not mainly led by nurses. A total of 23 articles were included in the scoping review 18–40 Figure 1. presents this scoping review study screening process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this can maximize the utility of limited resources available in rural areas. [ 10 ] Furthermore, this mode also allows the patients to avail eye care near their homes and avoid the significant burden of travel and loss of daily wages. Thus, it can prove to save time, cost, and effort for both patients and experts.…”
mentioning
confidence: 99%